That-which-new media studies-will-become - Phillip Roe (Fibreculture Journal, 2003)
This paper engages with the question of how new media can be thought as "new" when new media are nothing new. Through the concepts of virtuality (Deleuze), spectrality (Derrida) and projection (Heidegger), the paper offers offers some ways to think this question. The instance of photography is used to demonstrate the central thesis of the paper: that a new medium is always in advance of itself the emergence of particular technologies is always a result of discursive desires manifesting within culture prior to the technologies themselves. The paper proposes that we can approach the emergence of new media (technologies) in the same way, and offers the hologram as an instance that is attempting to manifest a post-print textuality a culture of writing-to-come. It proposes that new media studies must think this virtual time in order to engage with the question of the "new" of new media as a productive engagement with culture and new media technologies.